Новый ультратвердый поликристаллический композиционный материал - Шульженко, А.А.; Ашкинази, Е.Е.; Соколов, А.Н.; Гаргин, В.Г.; Ральченко, В.Г.; Конов, В.И.; Александрова, Л.И.; Богданов, Р.К.; Закора, А.П.; Ткач, В.Н.; Заика, Н.И.; Власов, И.И.; et al. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
A new ultrahard polycrystalline diamond-based composite material (UHM) has been developed using a combination of high-pressure high-temperature (HPHT) sintering technique and
chemical vapor deposition (CVD) of diamond. The CVD diamond rods incorporated in a sintered
polycrystalline matrix form the reinforced material. The hardness of HPHT-treated (p = 8 GPa, T
= 1570 K) polycrystalline CVD diamond is found to strongly increase up to 140 GPa from initial
(for virgin sample) value of 77 GPa. Drilling tools made of UHM showed 6–14 times less wear rate
against the korostyshev grainite (XI drilling category) in comparison with standard AKTM tools.